Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm taking my first course in Probability and one of my homework problems is to prove that for any two sets: $$P(A \cup B) = P(A) + P(B) - P(A \cap B) $$

Note that the function $P$ is the probability of an event happening. From the third axiom, we are given that for any two disjoint sets, that is $ A \cap B = \emptyset$:

$$P(A \cup B) = P(A) + P(B)$$

My thought process follows from this third axiom, but I run into a problem near the end:

Since $A$ and $B$ are disjoint sets, $P(A)=P(A-B)$ and $P(B)=P(B-A)$, so

$$P(A \cup B) = P(A) + P(B)=P(A-B)+P(B-A)$$

From this, it appears that we are essentially taking the symmetric difference of A and B. This, to me, seems to be equivalent to:

$$P(A-B)+P(B-A)=P(A)+P(B)-P(A \cap B)$$

Hence, by my logic:

$$P(A \cup B) = P(A)+P(B)-P(A \cap B)$$

Which, in essence, doesn't care whether two sets are disjoint or not as we are subtracting the intersection of them. If the sets are disjoint, then the intersection is merely null. If they intersect, then we are removing the "extra pieces".

I feel like this is inadequate proof despite my ability to convince myself that it is true.. Where, if anywhere, did I go wrong?


share|improve this question

3 Answers 3

Here's how I'd do it:

Note that $$ (*)\quad P(A\bigcup B) = P(A \bigcup A^{c}B) = P(A)+P(A^{c}B)$$

Then since $B = AB \bigcup A^{c}B$ we get that

$$P(B) = P(AB) + P(A^{c}B)$$

or equivalently $$P(A^{c}B) = P(B) - P(AB)$$ Plugging this into $*$ gives the desired result and thus completing the proof. Hope that helps!

share|improve this answer

For any sets $A$ and $B$, we have the disjoint union

$$A \cup B = (A- B) \cup (A \cap B) \cup (B-A). $$

Then, by the axiom,

$$ P (A \cup B ) = P(A- B) + P(A \cap B) + P(B - A). $$

Since $ P (A-B)= P(A) - P(A \cap B)$ and $ P (B-A)= P(B)- P(A \cap B) $, the result follows.

share|improve this answer

Use these three facts to get started. If $C\subset D$ are events, $P(D - C) = P(D) - P(C).$ If $C$ and $D$ are any events $C\cup D = C \cup (D - C)$ is a disjoint union, and $D - C = D - (C\cap D)$.
Fool with this and you should be able to get it.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.